A revision of the genus Bombyciella Draudt, 1950, with description of a new species and a new genus (Lepidoptera, Noctuidae: Xyleninae) - Saldaitis, Aidas; Benedek, Balázs; Behounek, Gottfried; Stüning, Dieter (Zootaxa, 2014)
The small Noctuidae genus Bombyciella Draudt, 1950, is revised, based on type-material of its only two known species, Bombyciella talpa Draudt, 1950 and Bombyciella sericea Draudt, 1950. Bombyciella antra sp. n. from southwest China is described as a new species close to B. talpa, the type-species of Bombyciella. B. sericea is found to be different in most characters, not congeneric with B. talpa, and most closely related to the genus Euplexia Stephens and Chandata Moore. Therefore a new genus, Maxiana gen. n., is described for its inclusion. These genera belong to two different tribus in the subfamily Xyleninae, Xylenini (Bombyciella) and Phlogophorini (Maxiana gen. n.). The systematic placement within the two subfamilies is also discussed. Lectotypes for B. talpa and B. sericea are designated.